Pemanfaatan Media Sosial sebagai Media Pemasaran Produk dan Potensi Indonesia dalam Upaya Mendukung ASEAN Community 2015. (Studi Social Media Marketing Pada Twitter Kemenparekraf RI dan Facebook Disparbud Provinsi Jawa Barat) - Ita Suryani (Program Studi Ilmu Komunikasi, 2014)
Heading of ASEAN Community 2015, Indonesia should improve its role to increase Indonesian society to love local products, and to introduce Indonesian local products and potentials using internet and social media is the best solution.The benefits and importance of social media is highly because social media has become a major pillar in the delivery of information. Social media can be used for socializing programs and policies, introducing the product and the potential of Indonesia, restoring and enhancing the image of tourism; and moreover, social media can be used as a means of learning communities.The object of this research is social media account of Indonesian Ministry of Tourism and Creative Economy; and Department of Tourism and Culture, West Java. Using case study methods, these research concludes that a number of smart companies does not only use social networking media it as a marketing medium, but also as a supporter of business activity, simplify and strengthen the function of communication to the public.